IMPLEMENTASI MODEL PROBLEM SOLVING BERBANTUAN MEDIA KOMIK TEMATIK UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Devi, Indriani (Universitas Negeri Semarang, 2021)
The low ability of students' critical thinking due to the learning process does not apply innovative models or media. The learning process only listens to books and does practice questions, so students' critical thinking skills are not trained. Of the various problems, the solution that can be given is by applying the Problem Solving model aided by thematic comic media. This study aims to describe the improvement of critical thinking skills using the Problem Solving model aided by thematic comic media in class IV SD 1 Japan. This type of research is Classroom Action Research. This research consists of 4 stages namely planning, action, observation, and reflection. The research was conducted in 2 cycles with 2 meetings each cycle. The subject of the study was class IV Japan 1 elementary school in 2019/2020 with a total of 34 students. The results showed that the critical thinking ability of pre-cycle students obtained classical completeness of 8.80% with less criteria, the first cycle obtained classical completeness of 70.6% with sufficient criteria, whereas in cycle II obtained classical completeness of 88.24% with good criteria.